CONSTRUCTION RISK MANAGEMENT (Journal of Engineering, 2006)
In most of the construction projects, there are many events or risks may occur during the executionof project. These risks (e.g. the excess of project cost or the expected time, increasing the prices ofmaterial and labor, accidents, changes, engineering errors or omissions, bad quality, delay inreaching the facilities to the site, etc.) may effect negatively on the project and the parties.Therefore, these risks must be identified and assessed accurately to avoid or reduce the negativeeffects for these risks. The concept of risk is used to assess and evaluate uncertainties associatedwith an event or a process. A construction process includes many uncertainties, therefore, theconstruction project’s parties are becoming aware of the construction process and thus the riskswithin this process are seeking more and more clarification that all is being done to removeforeseeable risk and minimize unforeseeable risk. It is also becoming clear that generic approachesto the management of risk are maturing and becoming easier to apply.